Applications of Automated Identification Technology in EHR/EMR - Lidong Wang; Cheryl Ann Alexander (Intelektual Pustaka Media Utama, 2013)
Although both the electronic health record (EHR) and the electronic medical record (EMR) store an individual’s computerized health information and the terminologies are often used interchangeably, there are some differences between them. Three primary approaches in Automated Identification Technology (AIT) are barcoding, radio frequency identification (RFID), and biometrics. In this paper, technology intelligence, progress, limitations, and challenges of EHR/EMR are introduced. The applications and challenges of barcoding, RFID, and biometrics in EHR/EMR are presented respectively.DOI: http://dx.doi.org/10.11591/ijphs.v2i3.3300